Self-Reported Knowledge and Practices of Healthcare Workers on Occupational Exposure and Protection from Infectious Disease at the Military Hospital in Sierra Leone (Global Journal of Medical Research, 2018)
Abstract not found
Keywords: healthcare workers: occupational exposure and protection: knowledge: practices: sierra leone